Hasan Basori dan Kesenian Ludruk Marjinal di Sidoarjo, Jawa Timur - Dita Hendriani (Lembaran Sejarah, 2012)
This study is an attempt to explore the life of a ludruk actor named Hasan Basori. Ludruk is sort of teather typically attributed to East Java in origin and in character. Hasan Basori was the leader of a ludruk group Bintang Warna (Star of Colors). This study discusses a correlation between the figure of Hasan Basori and ludruk, and how he managed to maintain a degree of loyalty to his profession as a ludruk actor despite the very modest life he had to live for choosing the profession.As a rural actor, Hasan Basori and his cultural activities are hardly recorded in any written documents on ludruk. Thus, in the present study interview became an essential method to collect primary data, while written documents were used as secondary sources of data. This study was focused on Hasan Basori’s motivation for choosing the ludruk teather as a way of life, the artistic process of becoming a ludruk actor, and the characteristic figure of an actor.It seems that Hasan Basori took for granted his life as a ludruk actor. For him ludruk was his life and his life was for performing ludruk. He did not leave the ludruk stage although it earned him only a very simple living. Most of the time he had to take sidejobs in order to cover the daily life of his and his family. Even though it was extremely tough economically, Basori never ceased performing ludruk, thus showing his loyalty to the artistic process in his life. He managed the ludruk as an entertainment product caring for the progress in the trend of art, flexible towards various contexts of changes.